Climate change policy discontinuity and its effects on Australia's national electricity market. Issue 1 (10th July 2018) - Simshauser, Paul; Tiernan, Anne
Abstract: Australia's National Electricity Market (NEM) became unstable in 2016/2017 after 20 years of consistent performance. The South Australian grid collapsed on 28 September 2016 – Australia's first black system event since 1964. Wholesale prices in the region trebled to $120+/MWh; soon after Hazelwood power station announced its exit with just 5 months' notice. The problem spread as prices elsewhere doubled to $89/MWh from a long‐run average of $42.50. The NEM is experiencing a supply‐side crisis. Consistent with the requirement to decarbonise the system, aged coal‐fired generators are exiting but decades of climate change policy discontinuity has frustrated the entry of new plant. Long‐dated capital‐intensive asset industries like electricity supply anticipate a conventional policy cycle. What they have experienced instead is consistent with garbage can theory. Policy clarity may be emerging for only the second time in two decades. As with the NEM, its durability will depend on cooperative federalism. Abstract : This paper provides an overview of Australia's National Electricity Market (NEM) and reviews Australia's climate change policy. A quantitative analysis reveals the implications of two decades of policy discontinuity on the NEM. The analysis is theoretically contextualised via garbage can theory.